The Effect of Experiential Marketing on Customer Satisfaction in Malang Customer Products - Ijlal Setyoviyon; Liem Gai Sin (Journal of the Community Development in Asia (JCDA), 2020)
Recently, people's increasing interest in business has encouraged them to try their luck in it. The more similar businesses are established, the tighter competition in, especially for similar businesses. Company leaders must not be careless and need to continue to strive to keep the company remain superior and compete with other companies. To win the competition, the company must have a competitive advantage to continue to survive. One effort is focusing on the consumers by providing the experience that is felt from these contacts. Companies must be able to influence consumers by creating products or services that win over their heart. They will have unforgettable good memories; in exchange they will come back or make repeat purchases.